UNJUK KERJA BLOOD CARRIER BOX DENGAN THERMOELECTRIC COOLER PADA VARIASI TEMPAT PENGUJIAN - Ridho Fharozi; Awaludin Martin (Jurnal Sains dan Teknologi, 2022)
The process of distributing blood from the proper storage before transfusion requires a cooling unit that is able to maintain the temperature so that the blood can be maintained and not damaged before being transfused. To maintain the chemical and structural composition of the blood, it is done by storing it at a temperature of 2-6 °C and the distribution is carried at a temperature of 2-10 °C with a maximum transit time of 24 hours specifically for whole blood. To answer this problem, this research will test the ability of a box that is used as a container for the blood distribution process using a thermoelectric cooling system. Thermoelectric was chosen for use as a cooler in the blood carrier box because of its small shape so that it can be operated in a limited space and operates at a DC voltage of 12 Volts. Thermoelectric uses a peltier element with type TEC1-12706 with the coefficient of performance (COP) value based on the highest calculation result, namely 0.176. In testing, carried out variations in place, variations in blood temperature and cooling system conditions. which in testing according to the SOP for blood distribution, the blood carrier box is able to maintain a blood temperature of 2-4 °C. So that this initial research can conclude that this blood carrier box can be used to distribute whole blood.